(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This research seeks to explain the spaces inhabited by characters from the story Alegres, libres y ruidosas (2015) by Pedro Juan Gutiérrez. Thoughout the details provided by the narrator, we will review “tone operators”, determining their descriptive and inherent statements, concerning characters, the space in which they are realized by building a transgressor identity under the view poetics of the vulgar. In this sense, the characters are "desiring machines" that burst into reality with a systematic flow of decomposed liquids (sperm) that drag political, ethical and aesthetic residues present in contemporary Cuba. Thus, we could speak of an eminently political sex that does not occur denotatively in the story but in the metaphors constructed by those operators who fix the "tone" of the story (carefree, vulgar, libertarian). Finally, we postulate that the details function as "clues" of a secret story (the story of a trap) that works under the visible story told in the tale